Comparative Analysis of the Implementation of Open Banking Systems for Indonesia's 2025 National Payment System Vision - Yuliana; Arif Maulana (Sawerigading Law Journal, 2023)
Financial industry has been surrounded by digital technology that known FinTech. This current trend has significant influence which affect the way people interact with banking industry. Consequently, there must be backwards and benefits that following this situation. However, whether it will be a threat or opportunity depending on banks’ future to experience the new situation. In this paper will elaborate the option of bank to acquire or work with fintech firms in adjusting their position into financial disruption and retain the competition demand. Open banking is a start adjustment over Fintech constraints. Indonesia lately has started to build future vision for digital payment to support the balance between disruptive financial payment system dominated by fintech. Some countries have been working on implementing open banking, but it seems like other countries prefer to follow Australia than UK which has started earlier. Other jurisdictions such as Canada, Singapore and India are considering the Australian approach rather than the less expansive approach as has been initially taken in the UK (Australia delays launch of ‘open banking’ regime). Therefore, it would be an appropriate attempt for Indonesia to reach out the appropriate approach that might be able to be implemented based on Australia strategies and regulatory framework created particularly in review into Open Banking paper, considering that Indonesia is still in the stage. This paper aims to analyse how Indonesia (central bank of Indonesia) should implement open banking system, considering Australia Open Banking approach and implementation in the subject of data protection, data transfer mechanism (security standard) and transformation process into open banking system.